Research policy in supportive care and palliative care for cancer dyspnea. (11th December 2021) - Matsuda, Yoshinobu; Yamaguchi, Takashi; Matsumoto, Yoshihisa; Ishiki, Hiroto; Usui, Yuko; Kako, Jun; Suzuki, Kozue; Matsunuma, Ryo; Mori, Masanori; Watanabe, Hiroaki; Zenda, Sadamoto
Abstract: Background: Dyspnea is a common and distressing symptom in patients with cancer. To improve its management, multicenter confirmatory studies are necessary. Research policy would be useful in conducting these studies. Here, we propose a new research policy for the management of dyspnea in patients with cancer. Methods: The first draft was developed by a policy working group of 11 specialists in the field of supportive care or palliative care for dyspnea. Then, a provisional draft was developed after review by a research support group (the Japanese Supportive, Palliative and Psychosocial Care Study Group) and five Japanese scientific societies (Japanese Association of Supportive Care in Cancer, Japanese Society of Medical Oncology, Japanese Society of Palliative Medicine, Japanese Association of Rehabilitation Medicine and Japanese Society of Clinical Oncology), and receipt of public comments. Results: The policy includes the following components of research policy on dyspnea: (i) definition of dyspnea, (ii) scale for assessment of dyspnea, (iii) reason for dyspnea or factors associated with dyspnea and (iv) treatment effectiveness outcomes/adverse events. The final policy (Ver1.0) was completed on 1 March 2021. Conclusions: This policy could help researchers plan and conduct studies on the management of cancer dyspnea. Abstract : We propose a research policy for the management of dyspnea in patients with cancer. This policy could help researchers plan and conduct studies on the management of cancer dyspnea.